Impact of some social and clinical factors on the development of postpartum depression in Chinese women - Qing Li; Shunyu Yang; Ming Xie; Xiaoming Wu; Liping Huang; Weiqing Ruan; Yungang Liu (BMC, 2020)
Abstract Background Postpartum depression (PPD) is prevalent and may present major adverse impacts on mother and child health. According to previous studies, mostly from the western society, PPD may have complicated etiologies, such as genetic, social and psychological factors. The aim of this study was to explore the associations of some social and clinical factors, particularly those unique in Chinese, with significant PPD symptoms. Methods A sample of 556 pregnant women in their 36th to 40th gestational week were randomly recruited in a cross-sectional study using a self-reported questionnaire, which collected maternal sociodemographic and clinical information. During their 2nd to 4th postpartum months, 522 participants responded to our screening of significant PPD symptoms, based on a score of Edinburgh Postnatal Depression Scale ≥9. Results A total of 90 (17.3%) participants were identified with significant PPD symptoms, and the following factors were observed more frequently in women with significant PPD symptoms (PPD+) than with fewer symptoms (PPD−): intensive involvement of parents-in-law in a participant's life (living together with her, taking care of her, or discriminating against a female baby), lack of support from husband, cesarean delivery, and breast milk insufficiency (supplemented with formula). After multiple logistic regression analysis, parents-in-law's preference to baby boy while devaluing baby girl, dissatisfaction with husband's support, cesarean delivery, and mixed feeding were strongly associated with significant PPD symptoms. Conclusion The potential risk factors for significant PPD symptoms, i.e., "son preference" custom, cesarean delivery and mixed feeding, deserve confirmation in continued, especially clinical diagnosis-based longitudinal studies.